1998
DOI: 10.1007/s002470050382
|View full text |Cite
|
Sign up to set email alerts
|

Ossifying renal cell carcinoma

Abstract: In older children, ossifying renal cell carcinoma is a potential explanation for a network of well-organized, curvilinear high-attenuation areas in a renal mass. Since ossification of renal cell carcinoma is a favorable tumor marker that implies a less extensive resection, it is important to anticipate this tumor before surgical resection is undertaken.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 0 publications
0
13
0
Order By: Relevance
“…Unlike other cases in the literature, neither ossification nor calcification of RCC was observed in any preoperative imaging studies such as plain X-ray , CT scan, or MRI. To our knowledge, it is the first ossifying RCC case published in the English literature that was diagnosed initially on pathologic examination [1][2][3][4][5]. In contrast to the previously reported cases, the tumor in our case was not relatively large and did not contain any bone marrow elements [1][2][3][4][5].…”
Section: Discussionmentioning
confidence: 77%
See 4 more Smart Citations
“…Unlike other cases in the literature, neither ossification nor calcification of RCC was observed in any preoperative imaging studies such as plain X-ray , CT scan, or MRI. To our knowledge, it is the first ossifying RCC case published in the English literature that was diagnosed initially on pathologic examination [1][2][3][4][5]. In contrast to the previously reported cases, the tumor in our case was not relatively large and did not contain any bone marrow elements [1][2][3][4][5].…”
Section: Discussionmentioning
confidence: 77%
“…Although the first case was reported in 1938, its mechanism is still unclear [2][3][4]. However, in their case report Yamasaki et al suggested that ossification in RCC may result from the metaplasia of pluripotent stem cells into osteoblastic cells by the mechanism of paracrine secretion of bone morphogenetic protein 2 (BMP-2) from the tumor cells, like gastrointestinal tract glandular tumors with ossification [5].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations